2014
DOI: 10.1021/am500637n
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Degradation and Regeneration of Polymer Solar Cells with Different Cathodes

Abstract: A comparative degradation study of solar cells based on a bulk-heterojunction (BHJ) blend of poly(3-hexylethiophene) (P3HT) and phenyl [6,6] C61 butyric acid methyl ester (PCBM) with two different cathodes is reported. Poly(ethylene-dioxythiphene):poly(styrene sulfonate) (PEDOT:PSS) coated ITO electrodes were used as the anode, whereas Ca/Al and Ca/Ag electrodes were used as cathodes. Fully degraded devices were subjected to thermal annealing under inert atmosphere. The performance of degraded solar cells with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
1
12
0
2
Order By: Relevance
“…Moreover, at these higher temperatures the continued increase in g is primarily driven by a corresponding increase in FF. The close correlation of these recovery profiles as a function of temperature with those observed previously for corresponding P3HT:PCBM devices 22 indicate that the primary cause for the regeneration seen in the P3HT:ICBA devices is also the reversibility of the Ag oxidation process. Further the effect of repeated annealing (140 C) cycles in an inert atmosphere on the efficiency of pristine P3HT:PCBM and P3HT:ICBA solar cells was also investigated and is shown in Fig.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…Moreover, at these higher temperatures the continued increase in g is primarily driven by a corresponding increase in FF. The close correlation of these recovery profiles as a function of temperature with those observed previously for corresponding P3HT:PCBM devices 22 indicate that the primary cause for the regeneration seen in the P3HT:ICBA devices is also the reversibility of the Ag oxidation process. Further the effect of repeated annealing (140 C) cycles in an inert atmosphere on the efficiency of pristine P3HT:PCBM and P3HT:ICBA solar cells was also investigated and is shown in Fig.…”
supporting
confidence: 79%
“…For example, for devices with ITO anodes, In and Sn are observed to diffuse into the active layer upon annealing. 22 However, since the electrode structure is the same for both sets of devices the difference in the observed reduction in device performance seen here can only be attributed to changes in the active layer morphology and/or composition.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Thei nfluence of the charge-extraction barrier was observed to be greatly diminished upon annealing the devices at 140 8Cf or 4min, with ar emoval of the S-shaped kink in the J--V curves and an improvementi nd evice performance by an order of magnitude.T his observation is consistent with our previous research on degradation mechanismsi n P3HT:PCBMd evices,w hich found that degradation occurs followingacombinationo ft hree primary pathways: (1) cathodic oxidation, (2) active layer phase segregation, and (3) anodic diffusion, some of whichc an be reversed upon thermal annealing. [35] Given that the presence of an oxide charge-extraction barrier is the dominant reason for poor performance in sputtered devices,r emoving the conditions for its creation should provide ar oute towards viable sputtering of highly efficient devices on aR 2R scale without the need for additional processing to cure the sputtering damage.T he creation of an insulating oxide barrier during sputtering could potentially arise from two sources:( a) the presence of residual oxygen within the sample chamber during the sputtering process, (b) the impingement of pre-oxidizeda luminum from the outer layer of the target exposed to air during venting of the chamber to removet he previous samples.A ll OPV devices prepared for this study had been previously sputtered after as ingle pump-purge cycle prior to sputtering, with a5 s target activation period prior to sampled epositiontor emove the surface oxidized metal from the target. It was expected that with these conditions,t he partial pressure of oxygeni n the chamber (after evacuation to the level of 10 À6 mTorr) would be negligible and the surface-oxidized material would be removed prior to deposition on the sample.H owever, it was noted that thermally evaporated cathodes are typically fabricated inside an inert atmosphere glove box, thus the pump-purge cycle for evaporated cathodes typically occurs from am uch lower base partialp ressureo fo xygen.…”
Section: Resultsmentioning
confidence: 99%
“…The oxidation of the low work function metal electrode can also occur due to the exposure to oxygen . For some electrodes, such as Ca/Ag, recovery is possible after annealing in inert environment, while this is not the case for Ca/Al electrodes .…”
Section: Degradation and Stability Issues Of Polymer Solar Cellsmentioning
confidence: 99%